Victor and Georgina - Smits, Alice; Ellickson, Lee (The Netherlands, 2009)
The film follows two Ugandan transgender activists who talk about the challenges faced by the LGBT+ community in the country. As pressure outside grows and personal differences also surface, the common cause is put to a serious test.
Verzio Film Festival Submission
Keywords: Documentary films